Interictal acute psychoses in temporal lobe epilepsy during withdrawal of anticonvulsant therapy. - Sironi, V A (1979)
Acute interictal psychotic attacks during withdrawal of medication are described in two patients with temporal lobe epilepsy submitted to depth EEG study with a view to surgical treatment. The patients were on chronic treatment with clonazepam associated in one with phenobarbitone and in the other with phenobarbitone plus carbamazepine. Our observations suggest that the acute withdrawal of clonazepam, the plasma levels of which were monitored may play a part in producing psychotic attacks characterised by dysphoric manifestations, irritability, aggressiveness, anxiety, and hallucinations. These symptoms could be interpreted as a withdrawal syndrome.